2013
DOI: 10.1371/journal.pone.0060821
|View full text |Cite
|
Sign up to set email alerts
|

MACC1 Down-Regulation Inhibits Proliferation and Tumourigenicity of Nasopharyngeal Carcinoma Cells through Akt/β-Catenin Signaling Pathway

Abstract: The present study was aimed at investigating the expression of metastasis-associated in colon cancer 1 (MACC1) in nasopharyngeal carcinoma (NPC), its relationship with β-catenin, Met expression and the clinicopathological features of NPC, and its roles in carcinogenesis of NPC. Our results showed that MACC1 expression was higher in NPC cells and tissues than that in normal nasopharyngeal cells and chronic inflammation of the nasopharynx tissues, respectively. MACC1 expression was closely related to the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…For various cancer cell lines, MACC1 has proven to induce proliferation and inhibit apoptosis [65,66]. Furthermore, several studies have revealed MACC1 to induce EMT by increasing the mesenchymal phenotype markers vimentin and CD44 and suppressing the epithelial phenotype markers E-cadherin and α-catenin [66][67][68].…”
Section: Metastasis Enhancer: Macc1mentioning
confidence: 99%
See 1 more Smart Citation
“…For various cancer cell lines, MACC1 has proven to induce proliferation and inhibit apoptosis [65,66]. Furthermore, several studies have revealed MACC1 to induce EMT by increasing the mesenchymal phenotype markers vimentin and CD44 and suppressing the epithelial phenotype markers E-cadherin and α-catenin [66][67][68].…”
Section: Metastasis Enhancer: Macc1mentioning
confidence: 99%
“…Overexpression of Oct4 and Nanog contributes to the stem cell phenotype of tumor cells [70]. MACC1 is also involved in migration, invasion, and angiogenesis [65][66][67][71][72][73]. Additionally, overexpression of MACC1 facilitates tumor blood supply by inducing vasculogenic mimicry, the formation of vascular channels in the absence of endothelial cells and fibroblasts [69].…”
Section: Metastasis Enhancer: Macc1mentioning
confidence: 99%
“…It has been demonstrated that MACC-1 expression is correlated with c-Met expression in GC (79). Furthermore, silencing MACC-1 can inhibit VEGF-C/VEGF-D expression and thus inhibit lymphangiogenesis (80).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Previous studies have suggested that MACC1 is associated with the Akt and Ras/EPH receptor B2 signaling pathways (28)(29)(30). Zhang et al (28) demonstrated that MACC1 expression may affect the PI3K/Akt signaling pathway and the protein expression of matrix metallopeptidase (MMP)2 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (28) demonstrated that MACC1 expression may affect the PI3K/Akt signaling pathway and the protein expression of matrix metallopeptidase (MMP)2 and MMP9. Meng et al (30) revealed that pAkt was a key target gene of MACC1, and that pAkt expression was significantly suppressed by MACC1 downregulation in nasopharyngeal carcinoma cells. In the present study, downregulating MACC1 expression increased the expression of PTEN and decreased the phosphorylation of Akt in EC cells.…”
Section: Discussionmentioning
confidence: 99%